Vita Art Now. - Miles, Elza (Johannesburg : Johannesburg Art Gallery, 1989)
Brown, Daved James ; Hobbs, Philippa Anne ; Motswai, thomas Tommy Trevor ; Schönfeldt, Joachim Paulus ; Amaler-Raviv, Arlene ; Anderson, Ilona ; Arnold, Marion ; Baloyi, Vincent ; Bell, Deborah Margaret ; Brand, Kevin ; Breebaart, Andrew ; Cruise, Wilma ; De Wet Barend, Petrus ; Dietrich Keith, Hamilton ; Havenga, Marnus ; Henorain, Lea ; etc.
Vita Art Now, Johannesburg Art Gallery, Johannesburg, 03.05 - 18.06.1989
boek